Prevalence and associated factors of reduced bone mineral density in patients with idiopathic inflammatory myopathies. (21st May 2014) - So, Ho; Yip, Man Lung; Wong, Andrew Kui Man
Abstract: Aim: To determine the prevalence and identify the associated factors of reduced bone mineral density (BMD) in patients with idiopathic inflammatory myopathies (IIMs). Method: Existing patients diagnosed to have IIMs were recruited for measurement of BMD by dual energy X‐ray absorptiometry. Demographic, clinical and treatment variables of these patients were recorded. The prevalence of osteopenia and osteoporosis were calculated. Using multivariate analysis, the independent associated factors for reduced BMD were evaluated. Results: Thirty‐eight patients with IIMs completed the study with 32 (84.2%) being female. The mean age of the patients was 52.8 ± 13.0 years. Nine (23.7%) patients had osteoporosis and 18 (47.4%) had osteopenia. Multivariate analysis revealed female gender and low serum albumin levels at onset were associated with lower spinal BMD. For femoral neck, the factors associated with lower BMD were high Myositis Disease Activity Assessment Visual Analogue Scales (MYOACT) score and high cumulative prednisolone dose. Conclusions: Reduced BMD is prevalent in patients with IIMs. Female gender, low serum albumin level at onset, high disease activity and high cumulative corticosteroid dose appeared to be the independent associated factors. Regular assessment of BMD is advisable. The use of anti‐osteoporotic and steroid‐sparing agents should be encouraged.